1996
DOI: 10.1002/j.1460-2075.1996.tb00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Cis-element, oriR, involved in the initiation of (-) strand poliovirus RNA: a quasi-globular multi-domain RNA structure maintained by tertiary (‘kissing’) interactions.

Abstract: The key steps in the replication of the poliovirus genome, initiation of (‐) and (+) strands, require two different cis‐acting elements, oriR and oriL, respectively. It has been proposed that the spatial organization of these elements is maintained by tertiary (‘kissing’) interactions between the loops of two constituent hairpins. Here, the putative partners of the kissing interaction within the oriR of the full‐length poliovirus RNA were modified by site‐directed mutagenesis. The destabilization of this inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 35 publications
3
93
1
1
Order By: Relevance
“…For example, the bacteriophage R17 coat protein recognizes a hairpin containing the ribosome binding site for the phage replicase (22). Also, viral RdRps replicating full-length products from linear templates have been shown to require various structures on the 3Ј end of the RNA template to initiate accurate synthesis (23)(24)(25)(26). One fundamental difference between genomic and subgenomic RNA synthesis is that subgenomic initiation occurs internally in a manner analogous to DdRps.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacteriophage R17 coat protein recognizes a hairpin containing the ribosome binding site for the phage replicase (22). Also, viral RdRps replicating full-length products from linear templates have been shown to require various structures on the 3Ј end of the RNA template to initiate accurate synthesis (23)(24)(25)(26). One fundamental difference between genomic and subgenomic RNA synthesis is that subgenomic initiation occurs internally in a manner analogous to DdRps.…”
Section: Discussionmentioning
confidence: 99%
“…This region harbors a heterogeneous sequence, ranging between 42 nts in HRV and 317 nts in DHAV, in addition to a relative short polyA tail. Enterovirus 3 UTR RNA structure models suggest the presence of two stem-loops, with a kissing loop predicted in some instances (Pilipenko et al, 1996;Wang et al, 1999). Various studies support an active role for interactions between the 5 and 3 ends of the viral RNA in controlling picornavirus gene expression.…”
Section: Implications Of Long-range 5 -3 Viral Rna Interactions On Irmentioning
confidence: 99%
“…It has been reported by others that mutations which affect tertiary interactions (' kissing ' mutants) in the 3h UTR of poliovirus destroy virus viability (Mirmomeni et al, 1997 ;Pilipenko et al, 1996). We, therefore, constructed similar mutations aimed at disrupting the tertiary interaction, to assess whether the non-viability correlated with a decreased affinity for the cellular factor in the EMSAs (Fig.…”
Section: Mutations In the 3h Utrs Of Entero-and Rhinovirus Affect Hosmentioning
confidence: 99%
“…We have previously shown that the 3h UTR plays a role in the replication of enteroviruses since mutations predicted to destroy stem-loop structures in this region have a deleterious effect on virus replication (Rohll et al, 1995). Others have found evidence of tertiary structural interactions that seem to be essential for viability (Mirmomeni et al, 1997 ;Pilipenko et al, 1996). Determination of the precise structures required for virus function, however, is complicated by the fact that it is possible to construct viable chimeras of poliovirus containing 3h UTRs from related viruses with very different primary and predicted secondary structures.…”
Section: Introductionmentioning
confidence: 99%